Impact analysis of motor faults on the DC Bus in electric vehicle drivetrains - Pugin, Devon (Department of Electrical Engineering, 2026)
This study investigated the analysis of electric vehicle drivetrains in the presence of a motor fault within a powertrain. The investigation was conducted utilizing a test rig that facilitated the controlled implementation of known faults in induction motors connected to an electric vehicle powertrain configuration, thus enabling the application of various control methodologies. The induction motors employed in this study comprised a healthy baseline motor without faults, a motor with known inter-turn short faults of two distinct severities, and a motor with a known broken rotor bar fault. The motors were connected to a grid source to establish a baseline for comparison. In each scenario, the faults were analysed using motor current signature analysis (MCSA), Park's Vector Approach (PVA), Extended Park's Vector Approach (EVPA), and DC bus current analysis. The objective of this study was to analyse the effects of various faults and their manifestation on the DC bus of powertrains, specifically under transient speed conditions. The analysis of the results presented in this study indicates that the DC bus analysis demonstrates the presence of a fault in the case of an inter-turn fault in the motor in a significantly more consistent manner. This method, along with the EPVA, proved to be the most effective approach for identifying the presence of a fault within the powertrain across multiple control methodologies and motor load levels. It has been demonstrated that an inter-turn fault introduces additional harmonics at twice the fundamental frequency of the system on the DC bus current. This harmonic can serve as a fault indicator and may produce additional stress on the DC bus of the system for the intern-turn fault. The selected EVPA and DC bus analysis methods proved less conclusive when applied to a broken rotor bar fault; however, these techniques were utilized with a focus on specific harmonics based on the literature that emphasized the imbalance introduced through an inter-turn fault. These two techniques help illuminate the propagation throughout the powertrain as they are applied to different currents throughout the powertrain, with the EVPA being applied to the motor line current. The most significant finding was that the DC bus analysis indicated the presence of a fault through a substantial increase in the harmonic at twice the fundamental frequency of the DC bus current irrespective of the complexity of the control method employed. Although more sophisticated algorithms can address errors within a system, they are unable to conceal the presence of errors in the DC bus fully, particularly in the case of short inter-turn faults. Consequently, further research should be directed towards this methodology, as it may prove valuable in identifying a broader range of faults and providing essential information for mitigating the impact of these faults on the DC bus of electric vehicle powertrains.